Early-onset epileptic encephalopathy with hearing loss in two siblings with TBC1D24 recessive mutations. (March 2015) - Stražišar, Barbara Gnidovec; Neubauer, David; Paro Panjan, Darja; Writzl, Karin
Abstract: Background: Recent studies have shown that recessive mutations in the TBC1D24 gene cause a variety of epilepsy syndromes, DOORS syndrome and nonsyndromic deafness. Methods/Results: We report on two siblings with hypotonia, early-onset epileptic encephalopathy, and severe developmental delay. The patients presented with clonic and myoclonic jerks within 1 h after birth. The seizures were resistant to treatment. Audiologic examination showed bilateral sensorineural hearing loss in both siblings. Genetic analysis revealed compound heterozygous mutations in the TBC1D24 gene: a novel missense mutation c.32A > G (p.Asp11Gly) in exon 2 and a frameshift mutation c.1008delT (p.His336Glnfs*12) in exon 4. Conclusion: This report supports previous observations that mutations in TBC1D24 cause diverse phenotypes. In fact, early-onset epileptic encephalopathy with sensorineural hearing loss is an additional phenotype observed in patients with recessive TBC1D24 mutations.